Religion of islam - Klein, F. A. (Routledge revivals., 2015)
The book, first published in 1906, outlines the religious, ceremonial, civil and moral laws and regulations of Islam. The four sources from which the doctrines and precepts of Islam are founded are the Quran, the Sunna, the Ijma and the Qias. This title also interprets the principles of the four sources in respect to ilm, or positive knowledge, and fiqh, or understanding. It is with these aspects of Islamic theology and law that this book is concerned. This book will be of interest to students of theology and religious studies.